MULTIVARIATE ANALYSIS OF GENETIC DIVERGENCE AMONG INDIAN MUSTARD (BRASSICA JUNCEA L. CZERN & COSS) GENOTYPES IN RELATION TO OIL QUALITY TRAITS - KUMAR, BINOD; PANDEY, ANIL; KR. SINGH, SANJAY (The Bioscan, 2013)
The pattern of distribution of genotypes in different clusters exhibited that geographical diversity was not related to genetic diversity as genotypes of same geographical region were grouped into different cluster and vice-versa. Amongst seven, clusters II were mono-genotype clusters, whereas cluster IV was the largest having 16 genotypes followed by cluster III and V involved 12 and 5 genotypes, respectively. Maximum divergence exhibiting clusters II and VII may be utilized through inter varietal hybridization to exploit high degree of genetic diversity between them. Solitary genotypes (RAURD 172) in cluster II might have resulted from geographical barriers preventing gene flow or intensive selection for adaptive gene complexes. Noteworthy is that cluster V exhibited high cluster mean for palmitic acid, oleic acid and low erucic acid; Cluster VII show low value of cluster mean for linolenic acid, high value for linoleic acid and erucic acid; whereas, high value of cluster mean for stearic acid in cluster I and high cluster mean for linolenic acid and oil content showed in cluster II and VI respectively, reflected probability of getting better segregants and primary recombinants expected to more, in case if the genotypes of these clusters will be used in hybridization programme.